Zika Virus on YouTube: An Analysis of English-language Video Content by Source - Corey H. Basch; Isaac Chun-Hai Fung; Rodney N. Hammond; Elizabeth B. Blankenship; Zion Tsz Ho Tse; King-Wa Fu; Patrick Ip; Charles E. Basch (Korean Society for Preventive Medicine, 2017)
Objectives The purpose of this study was to describe the source, length, number of views, and content of the most widely viewed Zika virus (ZIKV)-related YouTube videos. We hypothesized that ZIKV-related videos uploaded by different sources contained different content. Methods The 100 most viewed English ZIKV-related videos were manually coded and analyzed statistically. Results Among the 100 videos, there were 43 consumer-generated videos, 38 Internet-based news videos, 15 TV-based news videos, and 4 professional videos. Internet news sources captured over two-thirds of the total of 8 894 505 views. Compared with consumer-generated videos, Internet-based news videos were more likely to mention the impact of ZIKV on babies (odds ratio [OR], 6.25; 95% confidence interval [CI], 1.64 to 23.76), the number of cases in Latin America (OR, 5.63; 95% CI, 1.47 to 21.52); and ZIKV in Africa (OR, 2.56; 95% CI, 1.04 to 6.31). Compared with consumer-generated videos, TV-based news videos were more likely to express anxiety or fear of catching ZIKV (OR, 6.67; 95% CI, 1.36 to 32.70); to highlight fear of ZIKV among members of the public (OR, 7.45; 95% CI, 1.20 to 46.16); and to discuss avoiding pregnancy (OR, 3.88; 95% CI, 1.13 to 13.25). Conclusions Public health agencies should establish a larger presence on YouTube to reach more people with evidence-based information about ZIKV.